Features of oxygen therapy in complex treatment purulent wounds in patients with diabetes mellitus 2 types - Sayfullayev, Sayfiddin; Rajabova, Muslimaxon; Shodiyeva, Malohat; Fayzullayeva, Gulnoza; Tojiboyeva, Shaxzoda; Davranova, A.D. (Science and Education, 2024)
The article gives the information about features of oxygen therapy in complex treatment purulent wounds in patients with diabetes mellitus 2 types.